2018
DOI: 10.1017/s002221511800107x
|View full text |Cite
|
Sign up to set email alerts
|

The use of an ostial stent does not increase the success rate of endoscopic dacryocystorhinostomy

Abstract: Compared with the use of a silicone tube alone, the addition of an ostial stent did not significantly increase the success rate of endoscopic dacryocystorhinostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Multiple studies have sought to determine whether the intraoperative use of a silicone stent is warranted for EDCR operations, with several determining that long-term outcomes do not differ significantly when comparing patients with and without stenting. 9,10,22 Indeed, in one previous report, Pseudomonas infections were found to arise more often in patients treated via the extended deployment of stents within the lacrimal sac, leading to higher rates of DCR failure. 23 The appropriate amount of time for stenting is not universally agreed upon, and silicone tubes have the potential to drive granulation and to thereby elevate failure rates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple studies have sought to determine whether the intraoperative use of a silicone stent is warranted for EDCR operations, with several determining that long-term outcomes do not differ significantly when comparing patients with and without stenting. 9,10,22 Indeed, in one previous report, Pseudomonas infections were found to arise more often in patients treated via the extended deployment of stents within the lacrimal sac, leading to higher rates of DCR failure. 23 The appropriate amount of time for stenting is not universally agreed upon, and silicone tubes have the potential to drive granulation and to thereby elevate failure rates.…”
Section: Discussionmentioning
confidence: 98%
“…Some surgeons have reported that stenting increases the success rate of this procedure; however, many studies have shown that there are no significant differences in outcomes as a result of stenting. 9,10 In the present report, we describe a lobulated pedicled nasal mucosal EDCR technique that allowed for temporary exposure of the maxillary bone above the lacrimal sac and NLD. Following operative completion, these flaps can be replaced, covering exposed bone and thus minimizing the risk of cicatricle stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve these problems, many scholars have proposed a lot of practical schemes for decades, such as adjusting the size and shape of bone pores, using Mitomycin at the ostium site, improving the ostium mode of valve, injecting hormone eye ointment at the ostium site and inserting lacrimal duct support [6,14,[19][20][21][22]. The effects of these operations are remarkable, and lacrimal sac decompression will also has a place in these options.…”
Section: Discussionmentioning
confidence: 99%